Benefits of the New Laboratory Methods of the Vigilance of the Health of Cienfuegos Population - Pedro Sánchez Frenes; Sara Hernández Malpica; María Jesús Sánchez Bouza (Universidad de las Ciencias Médicas de Cienfuegos, 2015)
The vigilance of laboratory is the one that is developed on the general population or selected groups by means of the use of tests stop to sieve some health problems. As a part of sanitary strategies of the country, the technologies of the Ultrmicroanalytic System with the aim of strengthen the vigilance of infectious, tumor, congenital disease, among others. Its diagnostic capability has been enlarged and diversified, granting to the work of this system, a new conception, constituting a fortress of the health system in each municipality.